Evaluasi Penerapan Sistem Informasi Manajemen Rumah Sakit (SIMRS) dengan Metode Hot Fit di RSU Mitra Sejati Medan - Hasibuan, Rapotan; Layli, Rayhan; Safitri, Dedek; Anastasya, Raihanis; Pertiwi, Cindy (Universitas Batanghari Jambi, 2024)
The Hospital Information System (SIMRS) is a system that integrates the collection, processing, reporting and use of data information needed to increase the efficiency and effectiveness of health services through better management at various levels of health services. The purpose of this research is to evaluate the implementation of the hospital management information system (SIMRS) at Mitra Sejati General Hospital with the Human Organization Technology (HOT) Fit Model method. The type of research used in this research is qualitative research with the Hot-Fit model method. The results of this study are that when viewed in terms of the human aspect, it is still not optimal, there are still many obstacles that occur in the field including the absence of an RME obligation, The organizational aspect is good, the hospital management has conducted training and is always holding retraining. The technological aspect is satisfactory enough for HR. Another obstacle that often occurs is related to the discipline of human resources for data input that is not in real time, SIMRS which is applied at Mitra Sejati General Hospital still has application deficiencies, the hospital management does not provide support in the form of repairs or strengthening the hospital network. Suggestions for hospitals need to develop medical records, HR discipline, develop existing SIMRS and improve network constraints.